2015
DOI: 10.1162/jocn_a_00758
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Musicianship on the Cortical Mechanisms Related to Separating Speech from Background Noise

Abstract: Musicians have enhanced auditory processing abilities. In some studies, these abilities are paralleled by an improved understanding of speech in noisy environments, partially due to more robust encoding of speech signals in noise at the level of the brainstem. Little is known about the impact of musicianship on attention-dependent cortical activity related to lexical access during a speech-in-noise task. To address this issue, we presented musicians and nonmusicians with single words mixed with three levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
41
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 60 publications
(103 reference statements)
11
41
0
3
Order By: Relevance
“…We provide the first random-assignment, longitudinal evidence for improved hearing in noise with music training, validating the relationship between music training and speech-in-noise perceptual advantages and indicating that this "musician advantage" observed in previous cross-sectional studies [4,9,10,57,58] is not simply a reflection of pre-existing differences between those who pursue music and those who do not. Further, we reveal this improvement in the context of an established and successful music program providing free, group music instruction to underserved children.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We provide the first random-assignment, longitudinal evidence for improved hearing in noise with music training, validating the relationship between music training and speech-in-noise perceptual advantages and indicating that this "musician advantage" observed in previous cross-sectional studies [4,9,10,57,58] is not simply a reflection of pre-existing differences between those who pursue music and those who do not. Further, we reveal this improvement in the context of an established and successful music program providing free, group music instruction to underserved children.…”
Section: Discussionsupporting
confidence: 74%
“…Further, musicians demonstrate enhanced auditory cognitive function such as working memory [32][33][34] and attention [6,35,36], as well as enhanced neural representation of speech when presented in acoustically-compromised conditions [6,8,9,[37][38][39][40]. These findings are consistent with the theoretical framework proposed by Patel suggesting that music training promotes adaptive plasticity in speech-processing networks [41].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Expertise with rhythmic processing, such as developed through musical practice, could potentially confer benefits for processing the rhythm and timing cues in speech. Several cross-sectional comparisons of musicians and non-musicians have revealed a musician advantage for perceiving speech in noise (Parbery-Clark et al 2009, 2011; Swaminathan et al 2015; Zendel and Alain 2012; Zendel et al 2015) when groups are matched for key factors such as age, sex and IQ. Further, recent research from our laboratory and others has revealed links between rhythm abilities and various language skills, including reading (Gordon et al 2015; Huss et al 2011; Strait et al 2011; Thomson and Goswami 2008; Tierney and Kraus 2013; Woodruff Carr et al 2014), suggesting that rhythm may play a role in the transfer from music to language processing (see also Shahin 2011).…”
Section: Introductionmentioning
confidence: 99%